Moringa oleifera seed extract: A halal friendly alternative water disinfection mechanism - Idris, Munirat Abolore; Hammed, Ademola Monsur; Jaswir, Irwandi; Jami, Mohammed Saedi; Jamal, Parveen (2016)
The availability of good potable water and proper sanitation are important for human health but over 1.2 billion people lack access to it particularly in developing countries. The conventional treatment of water consists of coagulation, flocculation, sedimentation, filtration and disinfection is used worldwide in the treatment of water. The use of chemicals have caused hazardous implications such as carcinogenic disinfection by products that are generally non-biodegradable. This is generally considered abominable in the eyes of Islamic law since a general principle of maṣlaḥah (public good) is the prevention of any harm (ḍarar) to humans. Hence, conventional methods of assuring potable water especially in developing countries are unsustainable. As a result of this, the use of organic coagulants, bio-adsorbents and disinfectants derived from plant materials such as water hyacinth, chestnuts and acorns, and Moringa oleifera seed cannot be overemphasized. Despite the extensive research done for its coagulation properties, very few studies have been done to determine its disinfectant ability to kill microbes in water. This study scientifically examine the seed extract of Moringa oleifera in order to determine its disinfection ability against E.coli. Statistical optimization using surface response methodology was done to determine the optimum dose of the seed extract during disinfection process. The result of the optimization process shows that the seed extract has disinfection ability that reduced the concentration of E.coli in water. Hence, plant materials particularly Moringa oleifera can be explored for sustainable low cost water disinfection process and treatment. This provides a ḥalāl-friendly alternative water disinfection mechanism which is not only legally permissible (ḥalāl) but exquisitely pure (ṭayyib) for general usage as it seeks to avoid any harm for humans. The study finds that such green technology should be further optimised as a viable alternative water disinfection mechanism which ultimately brings benefit to the people.